Influence of Shoe Mass on Performance and Running Economy in Trained Runners - Rodrigo-Carranza, Víctor; González-Mohíno, Fernando; Santos-Concejero, Jordan; González-Ravé, Jose Maria (Frontiers in Physiology, 2020)
Purpose: The aim of this study was to assess the effects of adding shoe mass on running economy (RE), gait characteristics, neuromuscular variables and performance in a group of well-trained runners. Methods: Eleven well-trained runners (6 men and 5 women) completed four evaluation sessions separated by at least 7 days. The first session consisted of a maximal incremental test where the second ventilatory threshold (VT2) and the speed associated to the VO2max (vVO2max) were calculated. In the next sessions, RE at 75, 85 and 95% of the VT2 and the time to exhaustion (TTE) at vVO2max were assessed in three different shoe mass conditions (control, +50g and +100g) in a randomized, counterbalanced crossover design. Biomechanical and neuromuscular variables, blood lactate and energy expenditure were measured during the TTE test. Results: RE worsened with the increment of shoe mass (Control vs. 100g) at 85% (7.40%, 4.409 ± 0.29 and 4.735 ± 0.27 kJ·kg-1·km-1, p = 0.021) and 95% (10.21%, 4.298 ± 0.24 and 4.737 ± 0.45 kJ·kg-1·km-1, p = 0.005) of VT2. HR significantly increased with the addition of mass (50g) at 75% of VT2 (p = 0.01) and at 75%, 85% and 95% of VT2 (p = 0.035, 0.03 and 0.03, respectively) with the addition of 100g. TTE was significantly longer (~22%, ~42s, p = 0.002, ES = 0.149) in the Control condition vs. 100g condition, but not between Control vs. 50g (~24s, p = 0.094, ES = 0.068). Conclusions: Overall, our findings suggest that adding 100g per shoe impairs running economy and performance in well-trained runners without changes in gait characteristics or neuromuscular variables. These findings further support the use of light footwear to optimize running performance.